The Introduction of Human Heme Oxygenase‐1 and Soluble Tumor Necrosis Factor‐α Receptor Type I With Human IgG1 Fc in Porcine Islets Prolongs Islet Xenograft Survival in Humanized Mice. Issue 1 (2nd October 2015) - Lee, H.‐S.; Lee, J.‐G.; Yeom, H. J.; Chung, Y. S.; Kang, B.; Hurh, S.; Cho, B.; Park, H.; Hwang, J. I.; Park, J. B.; Ahn, C.; Kim, S. J.; et al.
Abstract : Apoptosis during engraftment and inflammation induce poor islet xenograft survival. We aimed to determine whether overexpression of human heme oxygenase‐1 (HO‐1) or soluble tumor necrosis factor‐α receptor type I with human IgG1 Fc (sTNF‐αR‐Fc) in porcine islets could improve islet xenograft survival. Adult porcine islets were transduced with adenovirus containing human HO‐1, sTNF‐αR‐Fc, sTNF‐αR‐Fc/HO‐1 or green fluorescent protein (control). Humanized mice were generated by injecting human cord blood–derived CD34 + stem cells into NOD‐scid‐IL‐2Rγ null mice. Both HO‐1 and sTNF‐αR‐Fc reduced islet apoptosis under in vitro hypoxia or cytokine stimuli and suppressed RANTES induction without compromising insulin secretion. Introduction of either gene into islets prolonged islet xenograft survival in pig‐to‐humanized mice transplantation. The sTNF‐αR‐Fc/HO‐1 group showed the best glucose tolerance. Target genes were successfully expressed in islet xenografts. Perigraft infiltration of macrophages and T cells was suppressed with decreased expression of RANTES, tumor necrosis factor‐α and IL‐6 in treatment groups; however, frequency of pig‐specific interferon‐γ–producing T cells was not decreased, and humoral response was not significant in any group. Early apoptosis of islet cells was suppressed in the treatment groups. In conclusion, overexpression of HO‐1 or sTNF‐αR‐Fc in porcine islets improved islet xenograft survival by suppressing both apoptosis and inflammation. HO‐1 or sTNF‐αR‐Fc transgenic pigs have potential for islet xenotransplantation. Abstract : In an adult pig islet to humanized mouse transplantation model, overexpression of human HO–1 or sTNF–α–Fc in porcine islets improves islet xenograft survival by suppressing both early apoptosis of islet cells and inflammation.